2022
DOI: 10.1007/s40122-022-00383-z
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal Analgesia with Extended-Release Dinalbuphine Sebacate for Perioperative Pain Management in Upper Extremity Trauma Surgery: A Retrospective Comparative Study

Abstract: Introduction:Patients undergoing upper extremity fracture surgery (UEFS) commonly suffer from unbearable acute pain. Opioids remain the mainstay of moderate to severe pain alleviation, although there is a growing concern regarding the increasing trend in misuse and abuse. This study aimed to observe the safety and efficacy of dinalbuphine sebacate (DS), a novel extended-release analgesic, along with multimodal analgesia (MMA) for post-UEFS pain control.Methods: We retrospectively reviewed the records of patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Additionally, DNS led to significantly faster ambulation [ 90 ]. Another retrospective study by Zheng et al examining the efficacy of DNS as part of a multimodal analgesia regimen (parecoxib, acetaminophen, and celecoxib) in upper extremity trauma surgery showed that the proportion of patients requiring opioids for postoperative breakthrough pain was significantly lower in those treated with DNS [ 91 ]. Finally, Lee et al found that there was no statistically significant difference in pain scores when comparing preoperative DNS to postoperative morphine in a randomized study of 43 patients following laparoscopic cholecystectomy [ 92 ].…”
Section: Novel Opioidsmentioning
confidence: 99%
“…Additionally, DNS led to significantly faster ambulation [ 90 ]. Another retrospective study by Zheng et al examining the efficacy of DNS as part of a multimodal analgesia regimen (parecoxib, acetaminophen, and celecoxib) in upper extremity trauma surgery showed that the proportion of patients requiring opioids for postoperative breakthrough pain was significantly lower in those treated with DNS [ 91 ]. Finally, Lee et al found that there was no statistically significant difference in pain scores when comparing preoperative DNS to postoperative morphine in a randomized study of 43 patients following laparoscopic cholecystectomy [ 92 ].…”
Section: Novel Opioidsmentioning
confidence: 99%
“…Evidence suggests that between 35% and 70% of patients who have undergone elective and emergency surgery suffer from postoperative pain. In one of the largest studies of patients in surgical departments in the UK, it was found that 10.9 percent of patients experienced high-intensity postoperative pain, while 29.7 percent of patients experienced medium-intensity pain [1].…”
Section: Introductionmentioning
confidence: 99%
“…6 In addition, the feasibility of dinalbuphine sebacate injection integrated with postoperative multimodal analgesia was also fully demonstrated in several abdominal and orthopedic surgeries. [7][8][9] However, the amount of nalbuphine or dinalbuphine sebacate excreted in breast milk and its potential impact on breastfed infants are not well understood. Current risk and benefit evaluation is based on limited data for nursing mothers receiving nalbuphine injections.…”
mentioning
confidence: 99%
“…While its safety and efficacy have been established in the previous pivotal study in patients undergoing hemorrhoidectomy, the analgesic effect can last for approximately 7 days, and it has a tolerable safety profile 6 . In addition, the feasibility of dinalbuphine sebacate injection integrated with postoperative multimodal analgesia was also fully demonstrated in several abdominal and orthopedic surgeries 7–9 . However, the amount of nalbuphine or dinalbuphine sebacate excreted in breast milk and its potential impact on breastfed infants are not well understood.…”
mentioning
confidence: 99%